PREVENTING LOSS OF INDEPENDENCE THROUGH EXERCISE (PLIÉ) AND PAIRED PLIÉ: RESULTS TO DATE. (16th November 2018) - Barnes, D; Chesney, M; Duffy, J; Yaffe, K; Abrams, G; Whitmer, R; Mehling, W
Abstract: Preventing Loss of Independence through Exercise (PLIÉ) and Paired PLIÉ are unique integrative group movement programs that target abilities and neural mechanisms that are relatively well-preserved in people with dementia. PLIÉ includes 1-hour daycare center-based classes with up to 10 individuals with dementia, 3 days/week for 18 weeks + 4 monthly home visits. Paired PLIÉ includes 1-hour community-based classes with up to 5 dyads (people with dementia and their caregivers), 2 days/week for 12 weeks + 3 monthly home visits. We are currently performing randomized, controlled trials of PLIÉ (NCT02350127) and Paired PLIÉ (NCT02729311). This abstract presents results to date including feasibility (enrollment/retention), safety (adverse events) and satisfaction (anonymous surveys). We have enrolled 88 participants in PLIÉ and 30 dyads in Paired PLIÉ. Retention rates are good (82% PLIÉ; 87% Paired PLIÉ) with most withdrawals due to non-study-related health decline. Two possibly study-related adverse events resulted in withdrawal for PLIÉ (exacerbation of premorbid osteoporotic vertebral fracture; negative emotional reaction); none were reported for Paired PLIÉ. Overall satisfaction with both programs is high (mean 5-point Likert scale: 4.5 PLIÉ, 4.8 Paired PLIÉ). Participants are highly likely to recommend the program to others (mean 10-point Likert scale: 8.4 PLIÉ, 9.4 Paired PLIÉ). Most caregivers report observing physical, cognitive and/or emotional benefits for their loved ones and themselves. PLIÉ and Paired PLIÉ are promising integrative group movement programs for people with mild-to-moderate dementia that appear to be feasible, relatively safe and associated with high levels of satisfaction and caregiver-reported benefits.